Whole transcriptome analysis of breast tumors during neoadjuvant chemotherapy: association with response to preoperative chemotherapy. Additional material - M. K. Ibragimova; M. M. Tsyganov; N. V. Litviakov (Успехи молекулярной онкологии)
.